STEAM-Based Learning with Loose Parts for Developing Children’s Creativity at TK Nurul Qur’an Stabat - Parapat, Asmidar; Munisa, Munisa; Nofianti, Rita; Wulandari, Saputri (CV Raskha Media Group, 2025)
This study explores the implementation of STEAM-based learning integrated with loose parts media to develop early childhood creativity at TK Nurul Qur’an Stabat. The research was conducted in response to the increasing need for learning approaches that prepare young children to think critically, solve problems, and adapt to rapid technological development. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation to describe the real conditions of children aged 4–5 years before and during the application of STEAM activities using loose parts materials. The findings indicate that children’s creativity measured through their ability to generate new ideas, create original products, and modify existing formshad not developed optimally prior to the intervention. The implementation of STEAM with loose parts provided opportunities for children to explore, experiment, imagine, and create freely according to their ideas. The study concludes that STEAM-based learning using loose parts has strong potential to enhance early childhood creativity, supported by engaging activities that integrate science, technology, engineering, art, and mathematics. This approach also fosters children’s curiosity, collaborative skills, and problem-solving abilities. The research further identifies supporting and inhibiting factors in the implementation process, emphasizing the need for teacher competence, appropriate learning media, and a conducive environment to optimize children’s creative development.